(untitled) (Stato, Chiese e pluralismo confessionale, 2023)
The Institutions of Justice in “Praedicate Evangelium” * ABSTRACT: This paper deals with the novelties that the new constitution on the Roman Curia “Praedicate Evangelium” has introduced in the regulation of the tribunals of justice of the Apostolic See. The change of name, the order in which they are regulated, the competencies assigned to them, their independence, among others, are the topics treated here, as well as some consequences that derive from them. Resumen: 1. Organismos de justicia: orden de presentación y significado del nuevo título - 2. Los organismos de justicia como instituciones curiales - 3. La misión de los organismos de justicia - 4. Organismos ordinarios de justicia independientes entre sí - 5. La Penitenciaría Apostólica - 6. La Signatura Apostólica - 7. La Rota Romana - 8. Conclusión - Bibliografía.